Comparing creatinine clearance in 24 hour urine and Cockcroft-Gault formula to determine glomerular filtration rate in pregnant women attending a Lima hospital - Golac Malca, Mario (2016)
Glomerular filtration rate (GFR) is calculated by the endogenous creatinine clearance (DCE) in 24-hour urine, with limited collection and difficulties for patients. There are formulas proposed to estimate renal function. Objective. To use the Cockcroft-Gaul formula of glomerular filtration and to compare it with the chemical colorimetric method in pregnant women. Design. Observational, correlational, prospective and transversal study. Setting. Central Laboratory, Sergio Bernales National Hospital, Lima, Peru. Participants. Pregnant women. Methods. Using prior informed consent blood samples and 24-hour urine of 92 pregnant women between November 2015 and January 2016 were processed. The Pearson correlation coefficient was used to compare the DCE results obtained with the Cockcroft- Gault formula and the serum-24 hours urine. Results. The sample had a normal distribution analyzed by Kolmogorov-Smirnov estimator. The average DCE in 24 hours urine was 73.65 ± 19.85 mL /min, and that obtained by the Cockcroft-Gault formula was 99.82 ± 18.75 mL/min, with t test significant difference in related samples (p <0.000); the correlation between these laboratory methods was low (r = 0.561) in all pregnant women and by trimesters, showing lack of correlation with the coefficient of the Lin correlation-matching (ccc) (p <0.01). Sensitivity (S) was 0.50, specificity (Sp) 0.591, positive predictive value (PPV) 0.212 and negative predictive value (NPV) 0.881. Conclusions. The DCE obtained by Cockcroft-Gault with the DCE serum-24 hours urine in pregnant women had low correlation (r = [0.4 to 0.67]) with low levels of S, Sp, PPV and NPV, so it is not recommended for use in pregnant women.